2022
DOI: 10.1097/pcc.0000000000002907
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Ratios and Deficits in Injured Children With Life-Threatening Bleeding*

Abstract: To assess the impact of plasma and platelet ratios and deficits in injured children with life-threatening bleeding.DESIGN: Secondary analysis of the MAssive Transfusion epidemiology and outcomes In Children study dataset, a prospective observational study of children with life-threatening bleeding events. SETTING: Twenty-four childrens hospitals in the United States, Canada, and Italy.PATIENTS: Injured children 0-17 years old who received greater than 40 mL/kg total blood products over 6 hours or were transfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…36,37 More recent multicenter studies using larger databases have shown improved survival in injured children who receive balanced resuscitation. 14,[38][39][40][41] A recently published multicenter, prospective, observational trial (MATIC [MAssive Transfusion In Children] study) found that high FFP/RBC ratios (>1:2) were associated with decreased 6-hour mortality compared with lower ratios (OR, 0.12; 95% CI, 0.03-0.52; p = 0.004) after adjusting for Pediatric Risk of Mortality score, cardiac arrest, use of vasoactive medications, and blunt mechanism. Spinella et al 41 also reported the plasma deficit (RBC volume minus plasma volume) and platelet deficit (RBC volume minus platelet volume), which provide additional perspectives on the balance of resuscitation and may be more sensitive markers of the effectiveness of balance resuscitation compared with blood product ratios.…”
Section: Balanced Resuscitationmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 More recent multicenter studies using larger databases have shown improved survival in injured children who receive balanced resuscitation. 14,[38][39][40][41] A recently published multicenter, prospective, observational trial (MATIC [MAssive Transfusion In Children] study) found that high FFP/RBC ratios (>1:2) were associated with decreased 6-hour mortality compared with lower ratios (OR, 0.12; 95% CI, 0.03-0.52; p = 0.004) after adjusting for Pediatric Risk of Mortality score, cardiac arrest, use of vasoactive medications, and blunt mechanism. Spinella et al 41 also reported the plasma deficit (RBC volume minus plasma volume) and platelet deficit (RBC volume minus platelet volume), which provide additional perspectives on the balance of resuscitation and may be more sensitive markers of the effectiveness of balance resuscitation compared with blood product ratios.…”
Section: Balanced Resuscitationmentioning
confidence: 99%
“…14,[38][39][40][41] A recently published multicenter, prospective, observational trial (MATIC [MAssive Transfusion In Children] study) found that high FFP/RBC ratios (>1:2) were associated with decreased 6-hour mortality compared with lower ratios (OR, 0.12; 95% CI, 0.03-0.52; p = 0.004) after adjusting for Pediatric Risk of Mortality score, cardiac arrest, use of vasoactive medications, and blunt mechanism. Spinella et al 41 also reported the plasma deficit (RBC volume minus plasma volume) and platelet deficit (RBC volume minus platelet volume), which provide additional perspectives on the balance of resuscitation and may be more sensitive markers of the effectiveness of balance resuscitation compared with blood product ratios. 42 After adjusting for age, Pediatric Risk of Mortality score, cardiac arrest, and mechanism of injury, increased plasma deficit (RBC mL/kg minus plasma mL/kg) was associated with increased odds of 6and 24-hour mortality by 10% and 20%, respectively, for every 10 mL/kg plasma deficit (p = 0.04 and p = 0.02, respectively).…”
Section: Balanced Resuscitationmentioning
confidence: 99%
“…Details regarding this cohort have been previously published [1]. An analysis of blood product ratios and deficits in children with traumatic injury from this dataset is detailed in a separate publication [18]. Data before the haemorrhage were gathered in the 24 h before the start of the bleed, and data during the event spans initiation (MTP activation or administration of first blood product if not under MTP) to the conclusion (MTP deactivation or last product with no more in the subsequent 60 min).…”
Section: Methodsmentioning
confidence: 99%
“…While there is no clear consensus regarding the benefits of a balanced resuscitation strategy in pediatric trauma, recent retrospective studies demonstrate decreased 24-h mortality using a balanced ratio transfusion approach. 23,24 Prospective data from Spinella et al 25 and the Massive Transfusion in Children (MATIC) investigators report that a balanced ratio transfusion strategy (plasma:erythrocyte ratio greater than 1:2) may improve early survival in children with life-threatening bleeding. In the actively bleeding, hemodynamically stable pediatric patient, international perioperative goal-directed massive hemorrhage guidelines and critical bleeding protocols derived from expert consensus suggest maintaining hemoglobin level in the range of 7.0 to 8.0 g/dL in children and 9.0 to 10.0 g/dL in neonates.…”
Section: Pediatric Patients With Massive Hemorrhage or Critical Bleedingmentioning
confidence: 99%
“…In the actively bleeding, hemodynamically stable pediatric patient, international perioperative goal-directed massive hemorrhage guidelines and critical bleeding protocols derived from expert consensus suggest maintaining hemoglobin level in the range of 7.0 to 8.0 g/dL in children and 9.0 to 10.0 g/dL in neonates. 16,[25][26][27] Despite expert consensus panel agreement of 95 to 100%, Valentine et al 16 acknowledge that many of these international good practice recommendations are based on weak evidence due to lack of randomized controlled trials and due to studies influenced by survivorship bias. Thus, perioperative physicians must consider the challenges of dynamic fluctuations in the physiologic status of the bleeding child while weighing the risks and benefits of blood loss and blood product transfusion.…”
Section: Pediatric Patients With Massive Hemorrhage or Critical Bleedingmentioning
confidence: 99%